2022
DOI: 10.1038/s41598-022-08895-6
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of misuse of antibiotics among parents of children attending clinics in regional referral hospitals in Tanzania

Abstract: Parents are the important implementers on appropriate/inappropriate use of antibiotics, especially in the pediatric population. Limited studies have associated poor knowledge, attitude, and practice (KAP) among parents with antibiotics misuse. Therefore, this study was conducted to determine the parents’ KAP and factors associated with inappropriate use of antibiotics among Tanzanian children. A hospital-based cross-sectional study was conducted in 14 regional referral hospitals (RRHs) in Tanzania between June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 35 publications
(26 reference statements)
5
16
2
Order By: Relevance
“…Appropriate/inappropriate attitudes were classified analogically. The assumption was based on previously published literature [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Appropriate/inappropriate attitudes were classified analogically. The assumption was based on previously published literature [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in several studies, the misuse of antibiotics has been associated with their poor knowledge, attitude, and practice (KAP) [13,14]. Reports from Tanzania on rational use of antibiotics with reference to children are scarce, most confined in the Northern part of Tanzania [15][16][17], and others are focused on parents/caregivers [18,19]. These reports show, poor practices by healthcare workers, that translates to antibiotic overdosing ranging from 60-87% [17] treatment of viral infection with antibiotics 28-69% [17,20] and polypharmacy 15-30% [17,20], however they cannot be generalized to other regions of Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although parents are believed to be a determining factor for appropriate or inappropriate use of antibiotics among children, their practices and most of what they know or do not know concerning antibiotics is influenced by health care workers. This is evidenced by findings from parents (n = 2802) in one of the largest study in 14 referral regional hospitals in Tanzania, whereby only 10% and 16% of parents had good knowledge and positive attitudes, and the majority (82%) had poor practices on rational use of antibiotics for children [18]. Despite this, 86% and 77% reported dispensers and prescribers respectively to be their main source of antibiotic information.…”
Section: Introductionmentioning
confidence: 99%
“…Being financially challenged adds a layer of complexity towards implementation of ASPs; 37 poverty is known to contribute to AMR because the clinician may be forced to prescribe based on clinical presentation because the patient cannot afford to pay for the necessary laboratory investigation. 38 Moreover, the patient may opt for a different antibiotic because the one prescribed is expensive. 39 The growing burden of AMR is expected to continue to strain the limited resources with the escalating treatment cost as a result of morbidity and unavoidable long-hospital stays for treatment, 40 if no measures are taken to halt its progression.…”
Section: Discussionmentioning
confidence: 99%
“…The patients' rigid attitude regarding not conforming to the instructions provided by the healthcare workers is also reported elsewhere, and mass education is observed to reduce these practices. 22,38 Lastly, one of the activities to be performed in ASPs is training and capacity building of the healthcare workers, and according to the NAPAR this has been an ongoing activity since its launch in 2017. However, findings from the current study have shown limited training opportunities, in terms of who can access this training and selective CME, where most do not focus on ASP.…”
Section: Discussionmentioning
confidence: 99%